Oedema prevention in physiotherapy practice using Kinesiology Taping - Weronika Wicha (Kazimierz Wielki University, 2022)
Prophylaxis against edema involves the removal of excess lymph fluid from a specific area of the body. The presence of lymph accumulation, is a sign of abnormalities in the functioning of the lymphatic system, which has lost the ability to properly transport lymph. Swelling otherwise known as lymphedema is among the chronic diseases that adversely affect the functioning of human systems. Lymphedema is one of the most common disorders of the lymphatic system. Its correct function is to drain lymph into the lymphatic vessels, and from there it travels to the lymph nodes. Its malfunction is the failure to drain the lymph into the lymphatic vessels or the lymph nodes. As a result of the abnormal lymph circulation, swelling usually occurs in the lower and upper extremities. The swelling at first appears to be painless, but over time it becomes hard thus reducing the functional capacity of the limbs. Over time, the skin and subcutaneous tissue can become infected, which can affect the formation of a cancer such as lymphosarcoma. Increasingly, so-called dynamic Plastering is being used to assist and alleviate lymphedema. Kinesiology Taping (KT) otherwise known as dynamic patching enables the reduction of swelling by elevating the skin, thus increasing the surface area between the skin and fascia. This results in body fluids having more room to flow freely to the lymph nodes, and this reduces our swelling and lymph accumulation in the extremities.[2] The purpose of this paper is to show the use of  Kinesiology Taping to reduce lymphedema. The paper is based on a review of articles in reputable journals from past years.